Production of associated Y and open charm hadrons in pp collisions at √s=7 and 8 TeV via double parton scattering - Cheung, S; Evans, T; Gandini, P; Gauld, R; Greening, E; Hadavizadeh, T; Harnew, N; Hill, D; Hussain, N; Jalocha, J; John, M; Harnew, N; et al. (Springer Verlag, 2016)
Associated production of bottomonia and open charm hadrons in pp collisions at s=7 and 8 TeV is observed using data corresponding to an integrated luminosity of 3 fb−1 accumulated with the LHCb detector. The observation of five combinations, Y(1S)D0, Y(2S)D0, Y(1S)D+, Y(2S)D+ and Y(1S)Ds+, is reported. Production crosssections are measured for Y(1S)D0 and Y(1S)D+ pairs in the forward region. The measured cross-sections and the differential distributions indicate the dominance of double parton scattering as the main production mechanism.